2019
DOI: 10.1021/acsomega.9b00701
|View full text |Cite
|
Sign up to set email alerts
|

One-Pot Synthesis of Nucleoside-Templated Fluorescent Silver Nanoparticles and Gold Nanoparticles

Abstract: In this study, a simple one-pot method was proposed to synthesize water-soluble nucleoside-templated fluorescent silver nanoparticles (Ag NPs) and gold nanoparticles (Au NPs). The nucleoside-templated fluorescent Ag NPs and Au NPs were further characterized by transmission electron microscopy (TEM), Fourier transform infrared spectroscopy (FTIR), and fluorescence spectroscopy (FLS). The effects of the molar ratio of reactants, reaction environment, and nucleotides on the synthesis of Ag NPs and Au NPs were als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 32 publications
1
4
0
Order By: Relevance
“…It has been found that the process is sensitive to the mixture stoichiometry, the order of mixing, and even UV illumination during the synthesis. Similar fluorescent AuNCs have been obtained in the presence of other nucleotides with ascorbic acid as a reducing agent [13]. Moreover, nucleotide-assisted synthesis can be used to better understand the mechanism of AuNC formation in the presence of DNA molecules without any external reducing agent, as recently reported in [14].…”
Section: Introductionsupporting
confidence: 61%
“…It has been found that the process is sensitive to the mixture stoichiometry, the order of mixing, and even UV illumination during the synthesis. Similar fluorescent AuNCs have been obtained in the presence of other nucleotides with ascorbic acid as a reducing agent [13]. Moreover, nucleotide-assisted synthesis can be used to better understand the mechanism of AuNC formation in the presence of DNA molecules without any external reducing agent, as recently reported in [14].…”
Section: Introductionsupporting
confidence: 61%
“…The characteristic peaks around 1394 and 1591 cm –1 are for the symmetric and antisymmetric stretching of COO – in Na-Cit. These peaks were observed in the Fe 3 O 4 NPs with a slight shift, which indicated the presence of Na-Cit on the surface of Fe 3 O 4 NPs . The attachment of Na-Cit on the surface of Fe 3 O 4 NPs prevents the aggregation of NPs, ensuring good dispersibility of the NPs in water.…”
Section: Results and Discussionmentioning
confidence: 97%
“…It is well-known that classical gold (Au), copper (Cu) and silver (Ag) nanoparticles (NPs) show localized surface plasmon resonance (LSPR) in the nanometer range size, which can be identified as a characteristic band in UV-visible spectra [ 2 , 3 ]. For synthesis, several approaches can be found in the literature [ 4 ], but over the last few years, green chemistry methods [ 5 , 6 , 7 ] have become of interest considering the possible biomedical applications of these nanostructures [ 8 , 9 ]. In these procedures, mild conditions are used to produce biocompatible and stable colloidal systems.…”
Section: Introductionmentioning
confidence: 99%